Genotype relationships in the CYP3A locus in Caucasians - Dally, Heike; Bartsch, Helmut; Edler, Lutz; Schmezer, Peter; Spiegelhalder, Bertold; Dienemann, Hendrik; Drings, Peter; Kayser, Klaus; Schulz, Volker; Risch, Angela (Cancer letters, 2004)
Genetic polymorphisms of the human CYP3A family affect clinical drug efficacy and may modify cancer risk. CYP3A genes show high sequence similarity that had previously lead to misallocation of CYP3A polymorphisms. Recent studies indicated a high degree of or even complete linkage for certain CYP3A alleles. Reliable LightCycler-based genotyping methods were developed and their degree of linkage in a large Caucasian population (n=1210) investigated. Strong linkage disequilibrium was confirmed between CYP3A4, CYP3A5, and CYP3AP1 (each at P<10−5). Contrary to some previous results claiming complete linkage between the phenotypically relevant CYP3A5*1 and a variant in a pseudogene promoter region CYP3AP1*1, we found among 428 controls (15 of 66) and 782 lung cancer cases (25 of 115) approximately 22% of CYP3AP1*1/*3 carriers to be homozygous for CYP3A5*3. We conclude that contrary to previous assumptions, the CYP3AP1 genotype is not a reliable predictor for CYP3A5 activity.
Gesehen am 11.12.2020